Evaluation of volume of drained rainwater in a housing project: case study in Londrina - PR - Bucharles, Luciano Gardano Elias (ANTAC - Associação Nacional de Tecnologia do Ambiente Construído, 2008)
The urban growth, especially resulting from the development of social interest housing projects of high population density, demands a substantial increase in the availability of public services. However, there is little information concerning the consequences of those projects. This article presents an analysis of rainwater drainage in a specific social interest housing project, by the assessment of flood hydrograms in four distinct situations: before the construction of the project, considering the natural river-bed; after the construction of the project, without considering the design changes introduced by the dwellers; the actual situation, considering those design changes, which resulted in an increase of the impermeable area; the actual situation, but considering the construction of infiltration trenches. The study indicated that the construction of the project increased the volume of rain-water superficial flow in 1.127%. By contrast, the construction of individual infiltration trenches in each one of the 331 residential lots would reduce this volume in 41%. The cost of each trench (US$ 168) can be compensated by the cost reduction of the project public drainage system. Moreover, this solution would comply with the project environmental and sustainability requirements.